Drag Reduction Efficacy of CTABr and Nanosilica Particles Using Rotating Disk Apparatus (RDA) - Abdulbari, Hayder A.; Oluwasoga, Akindoyo Edward (AENSI Publishing, 2015)
Over the years, it has been proven an energy consuming and cost effective to transport fluid in pipe, efforts that have been made to investigate this have not yielded a consensus on the mechanism and principles behind such, polymers that have been used degrade and less effective over time, surfactant which are self repair are not as effective as the polymer, recent studies on this concept with other solid particles have majorly been concentrated in pipe, this work investigated the drag reduction efficacy of silica nanoparticle with cationic surfactant, CTABr in a rotating disk apparatus, it was observed that, these material can reduce drag by 50% and are mechanically stable after degradation. Before drag could be reduced with these materials, proper proportions on the materials should be selected.